Opening New Worlds of Information: Library Technology and Internet Access for Patrons with Disabilities - Deine-Jones, Courtney (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
As more libraries offer patron access to the Internet and other on-line services, they must consider the needs of patrons with disabilities who will be using their Internet links either from the library or from remote sites. In planning and implementing technological improvements to optimize access for all patrons, librarians and information specialists must take into account questions of both physical and intellectual access to electronic information. This paper addresses these issues from a pragmatic perspective, reviewing available options and suggesting strategies for improving access for people with various disabilities.